The Analysis of Coconut Market Value Chain - Arifin, Zainal Arifin (International Journal of Law Policy and Governance, 2022)
Purpose – This paper seeks to examine how the coconut market value chain is managed in order to develop agricultural economic performance in Indragiri Hilir, Riau Province. Methodology/approach – The method used in this paper is descriptive qualitative research and literature review. The data is collected from secondary sources that is credible related to the topic. The focus of this research is to find various legal theories, propositions, principles, or ideas that are used to analyse and solve the formulated research questions. Findings – From the data collected, it is found that the coconut market value chain in Indragiri Hilir run quite well. Although there are some problems faced by the coconut farmers, both coconut farmers and Local Government have tried their best to develop coconut exporting activity and to minimize the constraints in coconut market in Indragiri Hilir.